How the Use of Orange (Citrus sinensis) Peel Essential oil Affected the Growth Performance of Rainbow Trout (Oncorhynchus mykiss)? - Gültepe, Nejdet (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2018)
The most important portion of the aquaculture production with 40-60% of the operating expenses is the feed cost. The decline in natural fish stocks and the resulting increase in the cost of fish meal have led to feed producers and researchers to search for new and/or alternative raw materials for fish feed production. Orange peel essential oil (EO) contains 94.72% D-limonene. Four essential oil supplemented diets (0%, 0.5‰, 1‰ and 3‰) prepared for rainbow trout juvenile. Four groups fish were stocked 100 L aquarium (55 fish per aquarium) with free flow water system for triplicate study in 90 days feeding trial. At the end of the 90-days experimental feeding period; feed conversion ratio is importantly decreased, relative growth rate, specific growth rate and protein efficiency ratio are importantly increased at the 1‰ rate orange peel essential oil additives group (p<0.05).
Keywords: citrus sinensis, essential oil, rainbow trout; SF1-1100; TP248.13-248.65; Animal culture; Biotechnology; 14. Life underwater; 6. Clean water